Myelofibrosis Associated with Romiplostim Treatment in a Patient with Immune Thrombocytopenia - Maria Fernanda Gonzalez; Jonathan King Freeman (Case Reports in Hematology)
Immune thrombocytopenia is characterized by antibody-mediated platelet destruction and insufficient platelet production resulting in isolated thrombocytopenia in the absence of underlying cause. Despite many treatment options, low-to-intermediate rates of remission and high rates of resistance to treatment are seen. Approximately 20% of patients do not attain a hemostatic platelet count after splenectomy or after first- and second-line medical approaches. A new option in these cases is treatment with romiplostim. Bone marrow (BM) fibrosis has been reported in clinical trials with romiplostim. We report a case with marked reticulin fibrosis of the BM, worsening of cytopenias and dyserythropoiesis, and atypical megakaryocytes, which did not reverse following cessation of the drug. Although this could represent idiopathic myelofibrosis, unrelated to therapy, the pretreatment biopsy demonstrating no fibrosis combined with the concordant timing of the drug and fibrosis suggests the treatment with romiplostim may be causative.